DATA SOURCES FOR BUSINESS INTELLIGENCE - Naveen Kunnathuvalappil Hariharan (International Journal of Innovations in Engineering Research and Technology, 2018)
As organizations' desire for data grows, so does their search for data sources that are both usable and reliable.Businesses can obtain and collect big data in a variety of locations, both inside and outside their own walls.This study aims to investigate the various data sources for business intelligence. For business intelligence,there are three types of data: internal data, external data, and personal data. Internal data is mostly kept in databases, which serve as the backbone of an enterprise information system and are known as transactional systems or operational systems. This information, however, is not always sufficient. If the company wants to answer market and industry questions or better understand future customers, the analytics team may need tolook beyond the company's own data sources. Organizations must have access to a variety of data sources in order to answer the key questions that guide their initiatives. Internal sources, external public sources, and collaboration with a big data expert could all be beneficial. Companies who are able to extract relevant data from their mountain of data acquire new perspectives on their business, allowing them to become more competitive.